2012
DOI: 10.1182/blood-2011-10-383661
|View full text |Cite
|
Sign up to set email alerts
|

Influence of single nucleotide polymorphisms in factor VIII and von Willebrand factor genes on plasma factor VIII activity: the ARIC Study

Abstract: Factor VIII (FVIII) functions as a cofactor for factor IXa in the contact coagulation pathway and circulates in a protective complex with von Willebrand factor (VWF). Plasma FVIII activity is strongly influenced by environmental and genetic factors through VWF-dependent and -independent mechanisms. Single nucleotide polymorphisms (SNPs) of the coding and promoter sequence in the FVIII gene have been extensively studied for effects on FVIII synthesis, secretion, and activity, but impacts of non–disease-causing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
5
19
0
1
Order By: Relevance
“…Although we were able to detect the association of the A2 allele (minor allele frequency 0.05) after a conditional analysis, we were unable to detect several other less common alleles at ABO (30), likely because of their lower allele frequencies. The significantly associated SNPs at the VWF locus tag three of seven haplotype blocks, consistent with a similar analysis of the ARIC cohort (38,39). Although the causative SNPs are not yet at this point, they likely act via alterations in VWF biosynthesis, secretion, or clearance from plasma (40).…”
Section: Discussionsupporting
confidence: 79%
“…Although we were able to detect the association of the A2 allele (minor allele frequency 0.05) after a conditional analysis, we were unable to detect several other less common alleles at ABO (30), likely because of their lower allele frequencies. The significantly associated SNPs at the VWF locus tag three of seven haplotype blocks, consistent with a similar analysis of the ARIC cohort (38,39). Although the causative SNPs are not yet at this point, they likely act via alterations in VWF biosynthesis, secretion, or clearance from plasma (40).…”
Section: Discussionsupporting
confidence: 79%
“…Nevertheless, an independent case-control study subsequently demonstrated that a SNP in STXBP5 also constituted a novel candidate risk factor for VTE (Smith et al, 2011). Furthermore, Campos et al (2012) recently reported that four intronic SNPs within the F8 gene also significantly associated with plasma FVIII activity levels. Further studies will be required in order to define how such non-coding F8 gene polymorphisms influence FVIII levels.…”
Section: Alternate Possible Determinants Of Elevated Fviii:cmentioning
confidence: 99%
“…The ISTH-SSC VWF Online Database (http:// www.vwf.group.shef.ac.uk/vwd.html) lists~500 mutations and polymorphic variants that were associated with VWD [11]. Single nucleotide polymorphisms (SNPs) in exons, 5′ regulatory region and introns are also reported to influence levels of VWF antigen and FVIII activity in healthy subjects [12][13][14][15]. Some of these VWF SNPs are associated with an elevated risk of thrombosis [5,16].…”
Section: Introductionmentioning
confidence: 99%